Pengaruh Latihan Speed Play Terhadap Nilai Hematokrit Dan Kardiorespirasi Atlet Basket - Arimbi Arimbi; Arifuddin Usman; Poppy Elisano Arfanda; Sarifin Sarifin; Wahyana Mujari Wahid (Departement of Mathematics Education, 2024)
The purpose of this study was to determine the effect of regular exercise with the speed play method in increasing cardiorespiratory capacity and blood hematocrit levels in Pinisi basketball athletes. The research method used was the one-group pre-posttest design experiment. The instruments used in this study were the Multistage Test (MFT) for cardiorespiratory and hct meter to measure blood hematocrit levels. The results of this study found that the percentage of blood hematocrit after the intervention of the speed play training method for the Pinisi basketball athletes was 44.94% higher than the average hematocrit level before being given the speed play training method for the Pinisi basketball athletes, which was 41.64%. There was a change with an average value of 3.3% in per 100 mg of blood, meanwhile the average cardiorespiratory capacity after the implementation of the speed play training program in Pinisi basketball athletes was 43.49 ml/kg/minute, which means an increase from the average capacity cardiorespiratory training before being given speed play training in phinisi basketball athletes of 40.95 ml/kg/minute experienced an average change of 2.54 ml/kg/minute.